Spiritual Culture of Banjar Sultanate (Historical, Hermeneutic and Educational Approach) - Kamrani Buseri (Jurnal Ilmiah Peuradeun, 2017)
Culture and education are interconnected. If culture is to be preserved, transformed and transferred from one generation to the next, education in its broader sense is the key process of doing so. Each society or community group has its own culture as its distinctive characteristics. This culture contains values by which members of the society abide. Since the establishment of Banjar Sultanate in 1526, the Banjarese have developed spiritual culture which is reflected in material forms such as in houses shapes, process of cultivating rice in the paddy field, and other daily traditions. Besides, spiritual culture is also manifested in educational institution as well as in the attitude of its educators. As of today, these cultural values are still relevant to be developed, because they may become foundation of social behavior, especially for younger generation who are prone to influences of secularism, hedonism, and pragmatism.